PENGARUH UKURAN RAJANGAN KUNYIT (Curcuma domestica Val.) DAN LAMA PENYULINGAN TERHADAP RENDEMEN DAN KARAKTERISTIK MINYAK ATSIRI DENGAN METODE WATER AND STEAM DISTILLATION - , ISMAYANI, Ir. Agus Prasetyo, M.Eng.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Essential oil is known as volatile oil or flying oil which is produced from parts of plant (root, skin, trunk, leaf, fruit, seed and flower) by distillation, extraction or expression. The turmeric oil is produced from rhyzomes of curcuma plant (Curcuma domestica Val.) that is useful for human, especially in pharmacy, cosmetic and flavour. The aims of this research were to study the effect of slicing size of raw material and distillation time on yield and characteristics of turmeric oil included its chemical components. The quality of turmeric oil produced by water and steam distillation was also studied and compared by quality of turmeric oil standard. A combination treatment of size of raw material and distillation time was conducted for the experiment. Curcuma rhyzomes were sliced according to the size of 0.5 cm, 1 cm, 1.5 cm and 2 cm, while distillation time were 6 hours, 8 hours and 10 hours by water and steam distillation method were applied. The oil produced by each combination treatment was collected and analyzed the yield, chemical component by GC-MS, and its quality compare to the standard. The result indicated that size and distillation time significantly affected to the yield of oil but nonsignificantly affected to the characteristic of oil. The main chemical components of turmeric oil were ar-tumerone (53.38%), Î±-tumerone (14.84%), Î±-phellandrene (8.47%), 1.8-cineole (6.52%) ,terpinolene (2.22%) and zingiberone (1.13%). The physical characteristics of oil were yellow colour, average specific gravity was 0.9288, refractive index was 1.5057, optical rotation was -11.2965 and completely soluble in 90% alcohol solution. The quality of tumeric oil was parallel to that of standard of New Direction Aromatics and Ozone Naturals. Yield 2.99% of oil was at most obtained when treatment of slicing 0.5 cm in size combined to 10 hours distillation time to produced turmeric oil.